Wearables beyond borders: A case study of barriers to gait assessment in low-resource settings - Godfrey, A.; Aranda, C.; Hussain, A.; Barreto, M.; Rocha, T.; Vitorio, R. [UNESP] (Elsevier B.V., 2020)
Currently, there are major EU-based projects to better utilise wearables as useful diagnostic aids/tools in clinical settings as well for deployment in the home to capture ageing processes. To date, there has been little investigation of the translation of those tools beyond the geographical regions in which they were developed and implemented. Our objective was to examine pragmatic issues and challenges in the use of wearables in a diverse, low-resource, middle-income country like Brazil. We found barriers to their understanding and adoption converge on three themes: (i) regional inequalities; (ii) knowledge and resources; and (iii) trust. Current large-scale projects should consider the scalability and implementation of their methods, given those themes, facilitating a stratified and global approach to healthy ageing.
Keywords: Inertial sensors; Informatics; Low-resource; Objective assessment